OPPORTUNITIES OF PROBIOTIC TREATMENT IN COMPLEX THERAPY OF ANTIBIOTIC-ASSOCIATED DIARRHEA IN CHILDREN - A.N. Surkov ("Paediatrician" Publishers LLC, 2011)
Disorder of normal intestinal flora is widespread state in children with different types of somatic pathology. Intestinal disbiosis disturbs homeostasis, leads to significant disorders in function of other organs and systems. Thus the correction of intestinal disbacteriosis is an actual problem of clinical pediatrics, and different specialists meet this problem. One of common causes of intestinal disbiosis is antibacterial treatment. Almost all antimicrobial drugs influence gastrointestinal tract and their administration lead to dyspepsia and antibiotic-associated diarrhea. Normalization of intestinal microflora is significant stage of complex treatment of these pathological states in children. The choice of probiotic drug should be well grounded. The article presents main data on epidemiology, pathogenesis, clinical symptoms, diagnostics and treatment of antibiotic-associated diarrhea in children, efficacy of probiotic drugs is demonstrated.Key words: children, indigenous intestinal microflora, antibiotic-associated diarrhea, probiotics, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 132-136)